Academic Performance and the Role of Self-directed Learning, Self-esteem, and Grit among Nursing Students - Ryan Michael Flores Oducado (Poltekkes Kemenkes Semarang, 2021)
Background: understanding the factors affecting academic performance is important to support and promote the academic success of students. While there have been several studies on nursing students’ academic performance, the role of self-directed learning readiness, self-esteem, and grit among Filipino nursing students have not been well documented.Purpose: This study aimed to determine the relationship of self-directed learning readiness, self-esteem, and grit to the perceived academic performance of nursing students.Methods: This correlational research was conducted among undergraduate sophomore nursing students in a higher education institution in the Philippines using adopted research instruments. Spearman’s rho tested the correlation between variables.Results: The results indicated that self-directed learning readiness (rs=.360, p=.000), self-esteem (rs=.301, p=.000), and grit (rs=.186, p=.023) were significantly related to the academic performance of sophomore nursing students.Conclusion: psychological resources such as self-directed learning readiness, self-esteem, and grit contribute to students’ academic performance. Strategies that encourage self-directed learning, increase self-esteem, and cultivate grit are needed to support student's academic success in nursing school.